Haemangiomatous polyp of uterine cervix: a rare cause of post-coital bleeding – a case report. (Bangladesh Journal of Medical Science, 2019)
Cavernous haemangioma of uterine cervix is a very rare lesion. It is clinically significant due to its presentation of pervaginal bleeding mimicking many other neoplastic lesions. Occasionally it may leads to massive haemorrhage complicating to hypovolemic shock. Here we are presenting a rare case of cavernous haemangiomatous polyp of endocervix presented with postcoital bleeding in a 32 years old lady. Surgical removal is curable and also has been proved to control post-coital bleeding successfully in our case.Bangladesh Journal of Medical Science Vol.18(1) 2019 p.153-155